1988
DOI: 10.1161/01.str.19.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Relation between blood lipids, lipoproteins, and cerebrovascular atherosclerosis. A review.

Abstract: Epidemiologic studies have failed to demonstrate a consistent association between blood lipid concentrations and lipoprotein abnormalities and clinical manifestations, for example, cerebral infarction. If lipids do relate to atherosclerosis, then a possible explanation for this apparent contradiction is that risk factors for symptomatic cerebrovascular disease may not necessarily be the same as those for atherosclerosis in general, that is, the factors associated with the precipitation of the clinical event ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
2

Year Published

1990
1990
2002
2002

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(58 citation statements)
references
References 57 publications
1
55
2
Order By: Relevance
“…In fact, lipid associations with atherosclerosis of major intracranial arteries are similar to those with coronary arteries 36 and are clearly established with extracranial carotid arteries. 37 Our study shows that carotid thickening is associated with slightly greater proportional elevations in LDL-C than apoB. This differs from the pattern reported for CHD.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, lipid associations with atherosclerosis of major intracranial arteries are similar to those with coronary arteries 36 and are clearly established with extracranial carotid arteries. 37 Our study shows that carotid thickening is associated with slightly greater proportional elevations in LDL-C than apoB. This differs from the pattern reported for CHD.…”
Section: Discussioncontrasting
confidence: 99%
“…11 There is a strong inverse association between HDL cholesterol and risk of coronary heart disease. 16,17 An inverse relationship between HDL cholesterol and cerebrovascular disease has also been demonstrated, as well as between HDL cholesterol and carotid atherosclerosis, 18 although the results are not as consistent as those for coronary heart disease. The exact mechanism of the protective effect of HDL has been a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…28 Other studies have shown no correlation. 29,30 Animal studies have shown that plasmatic arterionecrosis, the causative lesion of hypertensive cerebral hemorrhage, follows upon medial muscle cell necrosis. The earliest cerebral arterial change seen in hypertensive rats was inhibited when these animals were fed a cholesterol and lard-supplemented diet.…”
Section: Study Limitationsmentioning
confidence: 99%